Stability and self-passivation of copper vanadate photoanodes under chemical, electrochemical, and photoelectrochemical operation. Issue 14 (21st March 2016) - Zhou, Lan; Yan, Qimin; Yu, Jie; Jones, Ryan J. R.; Becerra-Stasiewicz, Natalie; Suram, Santosh K.; Shinde, Aniketa; Guevarra, Dan; Neaton, Jeffrey B.; Persson, Kristin A.; Gregoire, John M.
Abstract : Self-passivation under operational conditions is observed for several copper vanadate photoanodes, demonstrating their viability for durable solar fuels devices. Abstract : Deployment of solar fuels technology requires photoanodes with long term stability, which can be accomplished using light absorbers that self-passivate under operational conditions. Several copper vanadates have been recently reported as promising photoanode materials, and their stability and self-passivation is demonstrated through a combination of Pourbaix calculations and combinatorial experimentation.